Pemberdayaan Masyarakat Dusun Bayor-bayor dalam Pengolahan Sampah Organik Rumah Tangga Menggunakan Komposter Ember Tumpuk: Empowering the Bayor-Bayor Hamlet Community to Manage Household Organic Waste Using Stacked Bucket Composters - Fahrul Islam; Haeranah Ahmad; Fajar Akbar (Poltekita: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to improve the knowledge and skills of residents in Bayor-Bayor Hamlet, Batupannu Village, in managing household organic waste into compost using stacked buckets. The implementation method consisted of several stages. The initial reflection stage involved coordination with the village government and data collection to identify the main problems. The second stage included participatory planning through Focus Group Discussions (FGDs) with the community to determine the intervention model and activity schedule. The third stage was the implementation phase, covering education, demonstrations, and hands-on compost-making using a participatory training approach. Monitoring was conducted through mentoring and regular visits to evaluate the implementation process. The results showed a significant increase in participants’ knowledge, with the average pre-test post-test score rising from 41.8 (min: 13.3; max: 73.3) to 66.2 (min: 46.7; max: 86.7), and the establishment of two model households independently managing organic waste. In conclusion, this activity effectively enhanced participants’ understanding of waste management. Motivation, self-confidence, and continuous support were key factors in the successful adoption of the technology. To ensure program sustainability, it is recommended to establish local environmental cadres supported by village policies through regulations and incentives.